2008
DOI: 10.1016/j.neulet.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in patients with chronic hepatitis C are correlated with elevated plasma levels of interleukin-1β and tumor necrosis factor-α

Abstract: Studies suggest that cytokines have a role in the biology of depression. In this study, we evaluated depression and cytokine levels in patients with and without chronic hepatitis C (HCV) to better assess how chronic infection alters cytokines levels and may contribute to depressive symptomotology. Twenty-three adults with (n = 16) and without (n = 7) HCV were recruited through the Portland VA Medical Center. Research participants were excluded for current substance abuse, psychotic disorder, liver cirrhosis, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 28 publications
4
86
0
Order By: Relevance
“…32 Otherwise, the role played by the host's immune response (especially cytokine-related effects) on psychiatric disorders in CHC should not be disregarded. 33 In addition to depression, CHC has been shown to be associated with other psychiatric comorbidities that may themselves contribute to a poorer HRQOL. 4,16,34 Despite the results of multivariate analyses in this study, the influence of anxiety disorder influence on the HRQOL of patients with CHC should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…32 Otherwise, the role played by the host's immune response (especially cytokine-related effects) on psychiatric disorders in CHC should not be disregarded. 33 In addition to depression, CHC has been shown to be associated with other psychiatric comorbidities that may themselves contribute to a poorer HRQOL. 4,16,34 Despite the results of multivariate analyses in this study, the influence of anxiety disorder influence on the HRQOL of patients with CHC should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The immunologic response and incidence of depression in NCC must be evaluated. There is a strong suggestion that cytokines have a role in the biology of depression 28 . Th1 cytokines are predominant in the immunological response elicited by Cysticercus cellusae and include gamma interferon, interleukin-18 (IL-18), and the immunosuppressive, fibrosis-promoting cytokine transforming growth factor beta.…”
Section: Discussionmentioning
confidence: 99%
“…some interleukins) activated by IFN-α can play a role in the induction of depressive symptoms involving the serotoninergic system, hypothalamic-pituitarythyroid axis, and the cytokine network. [37][38] The relationship between ferritin and depression has rarely been studied. 39 Some reports indicated that chronic hemodialysis patients with major depression had higher ferritin levels.…”
Section: Discussionmentioning
confidence: 99%